Experience of the Commissioning and Implementation the Total Skin Electron Therapy (TSET) at Siriraj Hospital - Tuntipumiamorn, Lalida; Apipanyasopon, Lukkana; Liammukda, Piyanan; Krongyuth, Khammook; Kakanaporn, Chumpot; lampongpaiboon, Porntip; Vinijsorn, Surat (The ASEAN Journal of Radiology, 2023)
Objective: TSET at our institution has been commissioned. Technique and dosimetry were investigated and reported. Methods & Materials: According to the Stanford six-dual field technique, using a high dose rate (888 MU/min) mode 6 MeV electron, at 400 cm SSD, on Varian 23 EX linear accelerator, investigation for the optimal irradiation geometry and TSET dosimetric features were performed. Results: Acceptable field symmetry was obtained at the gantry angle ± 17.5° from 90°. Using a 1 cm perspex scatterer, the electron mean energy was degraded from 6 MeV to 2.1 MeV. Depth of dose maximum was detected at the surface to a depth of 2 mm. with R80 and R50 were at 0.52 and 0.9 cm from the surface. respectively. Absolute dose to water at a calibration point from the dual gantry in the high dose rate mode delivery was 1.367 Gy/1000 MU. The overlap factor (B) in this study was found to be 2.93. Phantom dosimetry revealed the accuracy of delivered dose was within ± 5%. Skin dose distribution was within ± 10%. of the dose at prescription point and the x-ray background dose averaged over a phantom body was 0.58%. Dose homogeneity over the patient’s flat surface varied only a few percents. But at the tangential surfaces, the 10-30% difference from the delivered dose were presented. Conclusion: TSET procedure for our first mycosis fungoides patient was successfully commissioned and implemented to the patient. Acceptable dosimetric features with the high dose rate electron mode were achieved. At one year follow-up, a satisfactorily clinical result was detected from the given technique.